Elizabeth Jennings: An Exile in her Own Country? - Ward, Jean (Literature and theology, 2007)
It is Catholicism, seen here as being somewhat alienated from the mainstream of English culture, that shapes Elizabeth Jennings’ sense of literary tradition, while Catholic beliefs and practice inform not only the themes and general outlook of her poetry, but arguably its forms and language also. Many of the concepts and experiences that Jennings’ poetry deals with are outside mainstream understanding; and the tension that results from such isolation is evident in her poetry. Nevertheless, Jennings constantly searches for community with the reader. The present study shows some of the methods by which, without resigning her untypical vision, she strives to give general significance to ‘local’ Catholic experience.